Unusual Space Weathering on a CE-5 Metal Grain Indicates Deceptive Surface Signatures of M-type Asteroids - Tian Zhang; Hong Tang; Xiongyao Li; Yuanyun Wen; Bing Mo; Wen Yu; Chuanjiao Zhou; Jianzhong Liu (The Astrophysical Journal Letters)
M-type asteroids are historically thought to be exposed metallic cores of differentiated planets with a composition dominated by pure iron and nickel. However, recent spectral and radar observations reveal an insufficient number of M-type asteroids in the main belt. Here, we report unusual space weathering characteristics associated with a natural metal grain found in Chang'e 5 lunar soil. Microcraters, impact glass, iron whiskers, and unique vesicular rims on the surface of this grain help to explain the unusual properties of some potential M-type asteroids, including low thermal inertia and density. Our findings indicate that space weathering processes, including micrometeorite bombardment and solar wind irradiation, conceal the real surface signatures of M-type asteroids. Furthermore, the presence of He and Ge alloy on the metal grain suggests that M-type asteroids are not only a large metallic Fe and Ni reservoir but also a potential source of noble gases and precious metals.